The configuration of the female characters in the polyphonic structure in The Cardboard house of Martín Adán - Castañeda Tantaleán, Shirley Janette (2022)
Martín Adán's cardboard house was developed at the beginning of the 20th century. His city characters remain in a distant, almost existential reality. The present work studies the configuration of the female characters in the polyphonic structure, a formal aspect that can be seen in this work. Following the contributions of Mijael Bajtin and Oswald Ducrot, a qualitative analysis of the text is carried out within the framework of literary theory, linguistic theory of enunciation and gender studies. The research concludes that a male speaker enunciates a conservative image of women that reinforces gender patterns sustained in social myths.